A study of edwardsiella tarda colonizing live asian clam, corbicula fl uminea, from Pasir Mas, Kelantan, Malaysia with the emphasis on its antibiogram, heavy metal tolerance and genetic diversity - Lee Seong Wei; Wendy Wee; Zalina Che Manan; Md. Ruhul Amin (2013)
This paper deals with the antibiogram, heavy metal tolerance and genetic properties of Edwardsiella tarda colonizing live Asian Clam, Cor bicula fl uminea from Pasir Mas, Kelantan, Malaysia. Asian Clam is a popular snack for Malaysians. An antibiotic susceptibility test was carried out using the disc diffusion method against 19 types of antibiotics, namely: oxolinic acid, ampicillin, erythromycin, lincomycin, oleandomycin, amoxicillin, colistin sulphate, sulfamethoxazole, chloramphenicol, doxycycline, fl orfenicol, fl umequine, kanamycin, nalidixic acid, novobiocin, tetracycline, fosfomycin, spiramycin and compound sulphonamides, whereas heavy metal tolerance of bacteria to Hg2+, Cd2+, Cr6+ and Cu2+ was tested using the two fold agar dilution method. The RAPD PCR profi le of the bacteria was characterized using three different types of universal primers. It was found that there were most cases of antibiotic sensitivity (56.1%), followed by antibiotic resistance (38.6%) and antibiotic intermediate sensitivity (5.3%). Only kanamycin was found to be able to inhibit all the bacterial isolates present, whereas other bacterial isolates were resistant to fosfomycin, lincomycin, novobiocin and sulphamethoxazole. Additionally, all bacterial isolates were also resistant to all the heavy metals tested. The bacterial isolates present showed a percentage of genetic similarity ranging from 37.5% to 100%. In conclusion, the fi ndings of the present study revealed that the sampled C. fl uminea were highly exposed to antibiotic and heavy metal residues